ISLAMIC COUNSELING FRAMEWORK FOR DEALING WITH AI-BASED DIGITAL GRIEF (BARZAKH DIGITAL) - Mawaddati, Arini; Maram, Ahmad Nabilul; Firtiyah, Lilis (Program Studi Bimbingan dan Konseling Universitas Tunas Pembangunan Surakarta, 2025)
The rapid emergence of Artificial Intelligence (AI) has led to the creation of